COVID-19 Vaccine Acceptance among Ajman Undergraduate Dental Students: A Cross-Sectional Study - M. A. Jaber; M. Abdelmagied; E. M. El-Ameen; K. I. Afrashtehfar (International Journal of Dentistry)
Background. Achieving widespread coronavirus disease 2019 (COVID-19) vaccination is crucial in controlling the pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This cross-sectional study aimed to identify factors associated with the willingness of dental medicine students to receive the COVID-19 vaccine. Objectives. The study sought to assess the knowledge, attitudes, and behaviors of undergraduate dental students toward COVID-19 vaccines and to identify determinants, motivators, and barriers to vaccine uptake and booster receipt. Methods. A web-based survey was distributed to all 882 undergraduate dental surgery students in January 2022, and 70.7% of the students responded. The survey used χ2 tests and logistic regression analysis to examine the association among the variables. The significance level was set at α = 0.05. Results. Most participants (72.4%) reported having adequate knowledge of COVID-19. The vaccine acceptance rate was higher among male and older trainees, with no significant difference compared to women and younger trainees with no significant difference (p=0.849). Acceptance of the vaccine varied according to study level (5-year program), ranging from 44.8% to 73.0%, in the following order 4th > 1st > 3rd > 5th > 2nd year. Social media (76.8%), government websites (66.5%), and family and friends (57.2%) were the main sources of COVID-19-related information. Among hesitant and unwilling participants, the main concerns were side effects (34.0%) and lack of understanding about the vaccine’s mechanism (67.3%). Conclusions. Ajman dental students had moderate knowledge of COVID-19 and obtained information mainly from social media, government websites, and family and friends. Age, sex, and study year influenced vaccine acceptance. The main reasons for refusal were lack of knowledge, fear of side effects, and complications. Education campaigns are needed to increase vaccine acceptance among dental students.